Diamond polishing - Schuelke, Thomas; Grotjohn, Timothy A. (Diamond and related materials, 2013)
The empirical know-how of single crystalline diamond polishing has been developed over centuries in the diamond gem cutting industry. Since the 1950s new and varied uses and potential applications for synthetically produced diamond have been consistently proposed and developed. This innovation process continues with the availability of ever better, more specialized and less costly single crystalline and polycrystalline diamond materials. Yet, the potential exploitation of this hardest of materials is still in its infancy. Polishing is a critical and limiting step for advancing diamond applications in terms of cost effective processing and the achievable material surface finish. The current state-of-the-art of polishing single crystalline and polycrystalline diamond materials is reviewed based on the published literature. The material removal process during traditional mechanical polishing using diamond grit and polishing wheels is strongly anisotropic and depends upon crystal planes and polishing directions. Wear debris analyses and molecular dynamic simulations led to the understanding that this anisotropy is primarily caused by a mechanically induced transition from diamond to an amorphous carbon phase rather than by microchipping as previously thought. Mechanical polishing also leads to subsurface damage and limits the achievable surface finish for single crystalline diamond. Advanced techniques are discussed to improve the polished crystal's surface quality. Mechanical polishing of polycrystalline diamond films and freestanding plates is particularly slow due to the intrinsic structure variations in such materials. To overcome these limitations faster polishing techniques have been developed and are reviewed and compared. These techniques introduce additional chemical and physical means of material removal extending the capabilities of mechanical polishing. There is no single method that can address all requirements, but the available variety affords the careful selection of an optimal process for a given task. Finally, while diamond polishing is a subject of interest since centuries, it still remains a very important research area required to unfold the promise of diamond as a technical material.